Preliminary survey of the herpetofauna of Marai Parai – Gurkha Hut, Kota Belud, Sabah - Seng, Evan Huat Quah; Alvinus Joseph; Paul Yambun Imbun (Sabah Parks Nature Journal, 2024)
Marai Parai at Mount Kinabalu is a well-known location that was explored by early naturalists. Many noteworthy discoveries were made in the past, especially involving botanical research. However, detailed studies on the herpetofauna of the area are lacking. A recent expedition by Sabah Parks to Marai Parai and associated areas resulted in the discovery of 21 species of frogs, four species of lizards and five species of snakes. This resulted in a total of 24 frog, four lizard and seven snake species reported from the area when combined with previously published records. The frogs composed of six families: Rhacophoridae (seven species), Bufonidae and Megophryidae (five species each), Dicroglossidae and Ranidae (three species each) and Microhylidae (one species recorded). Lizards composed of three families: Agamidae (one species), Gekkonidae (two species) and Scincidae (one species). Snakes comprised four families: Colubridae (four species), Pareidae, Elapidae and Viperidae (one species each). These findings reveal that Marai Parai and its associated areas are home to a diverse assemblage of amphibian and reptile species. The results of the study also indicate that the diversity of herpetofauna in the area is still underestimated as many new records were made. Research on the herpetofauna of Marai Parai and Mount Kinabalu in general should be supported as it will not only result in more discoveries, but also aid in the conservation of the species.